Beberapa Faktor Penentu Keberlanjutan Usaha Agroindustri Teh Rakyat - Patimah, Lusi; Trimo, Lucyana (Politeknik Negeri Lampung, 2019)
Agroindustry tea smallholder who still survive until now in the area of Bandung Regency, namely agroindustry tea small holder Farmer of Group Barokah in the Village of Lebak Muncang, Subdistrict Ciwidey. This agroindustry persisted, although experiencing various problems, among others: a) have not received help from the government for the factory, the processing machine is limited, b) the lack of supply of raw materials, c) unmet condition of factory hygiene, d) no SOP (Standard Operating Procedure) written, e) the distribution of products is limited, f) marketing is not yet wide, and g) the presence of new competitors who buy raw materials higher. The purpose of this study is to describe several factors determining the sustainability of agroindustry tea small holder. The research technique was conducted through case study. The determination of informant is done purposively that is: staff of the department of agriculture, vice chairman of Farmers Group, manager agroindustry tea folk, farmer suppliers. Secondary data is collected from: documents in related institutions and journals. Data and information obtained were analyzed descriptively. The results showed that several factors determining the sustainability of agroindustry tea small holderGroups of Farmers Barokah is: a) good product quality, b) the existence of grading process, c) the availability of raw materials continue, because the form of farmer, d) workers with a solid sense of family, e) finance is able to hire employees and buy raw materials in cash, f) customer loyalty, g) areas supportive for tea business activities, and h) promotional assistance from local government. Keywords: case study, standard operational procedure, tea business